2016
DOI: 10.1155/2016/7281585
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analyses Reveal Lipid Metabolic Process in Liver Related to the Difference of Carcass Fat Content in Rainbow Trout (Oncorhynchus mykiss)

Abstract: Excessive accumulation of carcass fat in farm animals, including fish, has a significant impact on meat quality and on the cost of feeding. Similar to farmed animals and humans, the liver can be considered one of the most important organs involved in lipid metabolism in rainbow trout (Oncorhynchus mykiss). RNA-seq based whole transcriptome sequencing was performed to liver tissue of rainbow trout with high and low carcass fat content in this study. In total 1,694 differentially expressed transcripts were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A drawback of our study is that it is mainly based on data from transcriptomic studies, and hence it may not precisely reflect metabolic fluxes (Chubukov et al, ). Nevertheless transcriptomic studies have previously led to the identification of metabolic pathways (Corominas et al, ; Hu, Gu, Sun, Bai, & Wang, ) and they are a sound approach to address brain metabolism in humans (Barros et al, ). Moreover, genomic‐based models have been extensively used to study metabolic networks (Duarte et al, ) and to simulate metabolic‐based phenotypes of cancer cells (Gruetter, Seaquist, & Ugurbil, ; Lewis & Abdel‐Haleem, ; Lewis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A drawback of our study is that it is mainly based on data from transcriptomic studies, and hence it may not precisely reflect metabolic fluxes (Chubukov et al, ). Nevertheless transcriptomic studies have previously led to the identification of metabolic pathways (Corominas et al, ; Hu, Gu, Sun, Bai, & Wang, ) and they are a sound approach to address brain metabolism in humans (Barros et al, ). Moreover, genomic‐based models have been extensively used to study metabolic networks (Duarte et al, ) and to simulate metabolic‐based phenotypes of cancer cells (Gruetter, Seaquist, & Ugurbil, ; Lewis & Abdel‐Haleem, ; Lewis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al found that in a mouse model, pharmaceutical inhibition of the fatty acid binding pathway reduced the symptoms of OA induced by a high-fat diet [65]. Also, lipid metabolism is a chemical reaction involving lipids, which are compounds soluble in organic solvents [66]. Park et al showed that the functional integrity of ABCD2 in modulating lipid metabolism was through the dysregulation of miR-141, and through ACSL4 in OA [67].…”
Section: Discussionmentioning
confidence: 99%
“…To study the underlying genetic mechanism and divergence in gene expression pattern between species, the gill transcriptome of both the Zebra fish and Tilapia in response to cold stress has analysed and identified the presence of divergently expressed genes in metabolic pathways, insulin signalling pathways, pyrimidine metabolism, apoptosis and FoxO signalling pathway among species (Hu et al . ). Transcriptome profiling of Tilapia was also carried out in response to alkalinity stress (Zhao et al .…”
Section: Current Status Of Transcriptomics In Aquaculturementioning
confidence: 97%